2015
DOI: 10.1371/journal.pone.0140293
|View full text |Cite
|
Sign up to set email alerts
|

Significance of PIK3CA Mutations in Patients with Early Breast Cancer Treated with Adjuvant Chemotherapy: A Hellenic Cooperative Oncology Group (HeCOG) Study

Abstract: BackgroundThe PI3K-AKT pathway is frequently activated in breast cancer. PIK3CA mutations are most frequently found in the helical (exon 9) and kinase (exon 20) domains of this protein. The aim of the present study was to examine the role of different types of PIK3CA mutations in combination with molecular biomarkers related to PI3K-AKT signaling in patients with early breast cancer.MethodsTumor tissue samples from 1008 early breast cancer patients treated with adjuvant chemotherapy in two similar randomized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 38 publications
6
19
0
1
Order By: Relevance
“…Clinical studies demonstrated 73%–83% concordance for PIK3CA status in ctDNA and archival tumor tissue, measured using PCR . Good concordance (approximately 90%) has been demonstrated among next‐generation sequencing, Sanger sequencing, and quantitative PCR for assessing wild‐type PIK3CA or mutations in exon 9 or 20 of PIK3CA . However, it should be noted that PCR‐based/hybridization methods or gene panels that focus on hotspot mutations may miss up to 20% of PIK3CA mutations .…”
Section: Methodsmentioning
confidence: 99%
“…Clinical studies demonstrated 73%–83% concordance for PIK3CA status in ctDNA and archival tumor tissue, measured using PCR . Good concordance (approximately 90%) has been demonstrated among next‐generation sequencing, Sanger sequencing, and quantitative PCR for assessing wild‐type PIK3CA or mutations in exon 9 or 20 of PIK3CA . However, it should be noted that PCR‐based/hybridization methods or gene panels that focus on hotspot mutations may miss up to 20% of PIK3CA mutations .…”
Section: Methodsmentioning
confidence: 99%
“…With this criterion, another 349 samples (15.5%) were considered as technically failed; finally, primary tumors from 1766 patients were eligible for statistical analysis (Figure 6). TP53 and PIK3CA NGS variants were orthogonally validated with dd-sequencing, as previously shown for this panel [67, 71]. …”
Section: Methodsmentioning
confidence: 99%
“…That observation was not reproduced in the clinic where PIK3CAm did not have any prognostic significance in a large group of predominantly lymph nodepositive breast cancer patients treated with adjuvant chemotherapy [19]. Similar results were obtained in the neoadjuvant setting.…”
Section: Pik3ca In Hormone Receptor-positive Breast Cancermentioning
confidence: 68%
“…Therefore, the clinical implication of PIK3CAm could, in part, depend on the specific hot spot mutation. The different hot spot mutations in PIK3CA have subtype predilection, with helical domain mutations more frequently observed in the molecular luminal A subtype and in lobular carcinoma, and kinase domain mutation (exon 20) more frequent in luminal B carcinoma as compared to other molecular subtypes or ductal carcinoma, respectively [11,17,19].…”
Section: Pik3ca Mutations In Breast Cancermentioning
confidence: 99%